Fostering engaged employees: the role of leadership and self-efficacy - Tripiana, Jacoba; Llorens, Susana (Anales de Psicología / Annals of Psychology, 2015)
This study examines the role of supporting leadership and self-efficacy in the development of work engagement. We evaluate the mediating role of self-efficacy between leadership and work engagement in a sample of 271 employees from a Public Administration (City Hall). Results from the Structural Equation Modeling Analysis reveal that self-efficacy mediates the relationship between leadership and work engagement. The perception of having supporting leaders relates significantly with employees’ self-efficacy, which in turns, positively relates to work engagement.